2020
DOI: 10.1192/bjo.2020.51
|View full text |Cite
|
Sign up to set email alerts
|

Real-world effectiveness of admissions to a tertiary treatment-resistant psychosis service: 2-year mirror-image study

Abstract: Background Treatment-resistant schizophrenia is a major disabling illness which often proves challenging to manage in a secondary care setting. The National Psychosis Unit (NPU) is a specialised tertiary in-patient facility that provides evidence-based, personalised, multidisciplinary interventions for complex treatment-resistant psychosis, in order to reduce the risk of readmission and long-term care costs. Aims This study aimed to assess the long-term effectiveness of treatment at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Also, in a mirror-image study, each patient serves as his or her own control, and observed changes from pre- to post-LAIs introduction may reflect regression to the mean. 57 Moreover, there are further biases in mirror-image studies, such as expectation biases, natural illness course, and time-effect. 25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, in a mirror-image study, each patient serves as his or her own control, and observed changes from pre- to post-LAIs introduction may reflect regression to the mean. 57 Moreover, there are further biases in mirror-image studies, such as expectation biases, natural illness course, and time-effect. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Fifth, owing to the nature of this study, we could not focus on the patients’ perspective or whether there was a specific component or components that yielded the positive outcome. 57 …”
Section: Discussionmentioning
confidence: 99%
“…This can be likely attributed to differences in clinical practice, especially as previous studies have highlighted clinician knowledge, experience, and confidence as a significant barrier to clozapine treatment [26]. For example, SLaM hosts several specialist services, including the National Psychosis Service, a tertiary referral service with a special interest in clozapine rechallenge for whom this is deemed to be safe, often in close liaison with other medical specialities such as haematology [27]. Recent geographical data has demonstrated a substantial variation in clozapine prescription rates in the UK, with suggestions for a national training programme for clinicians and the implementation of a 'Hub and Spoke' model to improve clozapine management practices [28][29][30][31]..…”
Section: Variation In Practicementioning
confidence: 99%
“…Nevertheless, this estimate is likely to be confounded by other differentials such as BEN [19]. In the second half of the twentieth century, neutropenia was defined as an ANC value less than 1500/μL in individuals after the age of one [28], statistically determined as two standard deviations below the population mean at the time [27]. However, this classification system was originally developed in a largely Caucasian population and has consequently been recognised to preclude those with haematological variants such as BEN [27,37].…”
Section: Ben and Clozapine Monitoring Guidelinesmentioning
confidence: 99%
See 1 more Smart Citation